{Dietary habits in adolescent girls with polycystic ovarian syndrome} - Eleftheriadou, M.; Stefanidis, K.; Lykeridou, K.; Iliadis, I.; Michala, L. (Gynecological Endocrinology, 2015)
© 2014 Informa UK Ltd. The phenotype of polycystic ovarian syndrome (PCOS) is known to worsen with weight gain, increased ingestion of carbohydrates and a sedentary lifestyle. The purpose of this study was to assess the dietary habits in a group of adolescent girls with PCOS. Adolescents with PCOS were recruited and asked to complete a questionnaire on their eating habits and a recall dietary diary, from which their caloric and macronutrient intake was calculated. Results were compared with those from a group of normal controls. Thirty-five women with PCOS and 46 controls were included. Girls with PCOS were less likely to have cereals for breakfast (20.7 versus 66.7{%}) and as a result consumed less fibre than controls. They were more likely to eat an evening meal (97.1 versus 78.3{%}) and eat this over an hour later when compared to controls. Despite having comparable body mass indexes, girls with PCOS ate a daily surplus calorie average of 3{%} versus controls that had a negative calorie intake of 0.72{%} (p=0.047). Ameliorating eating habits early in adolescence in girls with PCOS may improve future metabolic concerns related to a genetic predisposition and worsened by an unhealthy lifestyle.
Keywords: Adolescent health; Diet; Lifestyle; Metabolic syndrome; PCOS